2012
DOI: 10.1016/j.adolescence.2012.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational transmission of religious beliefs and practices and the reduction of adolescent delinquency in urban Thailand

Abstract: This study examines the intergenerational transmission of family religion as measured by parent’s and adolescent’s beliefs and practices in Buddhism, and its relation to delinquent behaviors among early adolescents in Thailand. The data set is from the Thai Family Matters Project 2007, a representative sample of 420 pairs of parents and teens in Bangkok. A structural equation model is employed for the analysis. The intergenerational transmission and the direct and indirect association between parents’ and adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 33 publications
2
15
0
4
Order By: Relevance
“…In 10 studies, predictors and mediators were individual-level RS variables. For example, religious beliefs (e.g., Chamratrithirong et al, 2013) and spirituality (Dowling et al, 2004) predicted religious involvement or overall RS, which in turn predicted youth outcomes. Inversely, in one study religious involvement predicted youth outcomes via spirituality (Kang & Romo, 2011).…”
Section: (Q4) Are Relations Between Rs and Youth Outcomes Causal?mentioning
confidence: 99%
“…In 10 studies, predictors and mediators were individual-level RS variables. For example, religious beliefs (e.g., Chamratrithirong et al, 2013) and spirituality (Dowling et al, 2004) predicted religious involvement or overall RS, which in turn predicted youth outcomes. Inversely, in one study religious involvement predicted youth outcomes via spirituality (Kang & Romo, 2011).…”
Section: (Q4) Are Relations Between Rs and Youth Outcomes Causal?mentioning
confidence: 99%
“…In contrast, family religiosity, a major protective factor representing the family environment, might also be transmitted from parents to their children and was related to a reduction in the children’s delinquent behaviors, particularly in early adolescence (Chamratrithirong et al 2013). Furthermore, results from research based on a sample of 342 heterosexual married couples indicated that religiosity plays an important role in the quality of the marriage indirectly as it appears to manifest itself in religious communication between partners, which in turn was directly linked to martial satisfaction (David and Stafford 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Research in social stratification has shown that parents' and children's educational attainment are still positively correlated despite the considerable decline of this association across birth cohorts (Breen et al 2009;De Graaf and Ganzeboom 1993). Evidence also suggests that church attendance and religious beliefs are transmitted from parents to children (Chamratrithirong et al 2013;Kelley and De Graaf 1997;Myers 1996;Vaidyanathan 2011;Voas and Storm 2012). Examining both applications in one study is partly motivated by the fact that the transmission of education has a genetic component, whereas this is unlikely to be the case for the transmission of church attendance (Plomin 1990).…”
Section: Introductionmentioning
confidence: 99%